The long-term performance of horizontal acquisitions - Capron, Laurence (Strategic Management Journal, 1999)
This paper examines how value is created in horizontal mergers and acquisitions. More specifically, it examines the impact of post-acquisition asset divestiture and resource redeployment on the long-term performance of horizontal acquisitions. The data come from a detailed survey of acquiring firm managers and cover 253 horizontal mergers and acquisitions that were initiated by European and U.S. firms in manufacturing industries for the period 1988–1992. This study incorporates insights from the cost efficiency and resource-based theories to propose a model of the effects of asset divestiture and resource redeployment on long-term acquisition performance. Overall, our results show that both asset divestiture and resource redeployment can contribute to acquisition performance, with, however, a significant risk of damaging acquisition performance when the divested assets and redeployed resources are those of the target. Copyright © 1999 John Wiley & Sons, Ltd.